Relational Architecture of Quality Assurance: Leadership, Work Systems, and Work Consistency in Islamic Vocational Education" A Conceptual-Analytical Review - Yusup Suffandi; Mohammad Makinuddin; Muhammad Muizzuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study examines the relational nexus among quality assurance, leadership, work systems, and work consistency within the context of Islamic vocational education. Employing a qualitative descriptive method with a library research (conceptual-analytical) design, the study synthesizes theoretical and empirical literature to map how these four constructs interact in supporting institutional quality culture. The findings indicate that visionary leadership grounded in prophetic values (uswah hasanah, amanah, and 'adl) functions as the principal driving force in cultivating a culture of quality within Islamic vocational institutions. A structured and measurable work system, anchored in clear standard operating procedures (SOP), serves as the operational bridge that translates quality-assurance policy into the institution's daily practice. Furthermore, work consistency, sustained through continuous evaluation and the collective commitment of all school members (amanah, itqan, and ihsan), is found to exert a direct influence on the improvement of graduate quality. The study also identifies the Plan-Do-Check-Act (PDCA) cycle as a practical mechanism through which management and quality-assurance functions complement one another, and shows that the interaction between quality-assurance strength and work-discipline strength produces four distinct organizational conditions. The study concludes that the success of quality assurance in Islamic vocational education is not determined solely by administrative regulation, but rather by the synergy between adaptive leadership styles, disciplined work systems, and a consistently internalized Islamic work ethic.